Abu Hamid Al-Ghazali on the Formation and Development of Economic, Social and Political Life - Orman, Sabri (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Abu Hamid Al-Ghazali on the Formation and Development of Economic, Social and Political Life